MODEL QUANTUM TEACHING MENGGUNAKAN MEDIA GAMBAR SERI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI KURIPAN WONOSOBO - Fajar Cahyadi; Pujiyati Pujiyati (Universitas PGRI Semarang, 2013)
?é?áThe problems revealed in this research is whether there is influence of Quantum Teaching Model by using Media of Picture Series toward Learning Outcomes Indonesian course of the fifth Grade in Kuripan State Elementary School